Local Wisdom Values and Religious Moderation in Islamic Boarding Schools - Zahrah, Fatimatuz; Amaliyah, Rahmatul (Jurnal Dialog, 2024)
Building religious moderation can be done in various ways, one of which is using local wisdom values. Local wisdom values can be implemented in learning in madrasas. This research was conducted at MTs Mambaul Ulum Bata-bata 1 to analyze local wisdom values used in building religious moderation, and efforts to build religious moderation using Madurese local wisdom values. A qualitative method with an exploratory descriptive design was used in this study. The informants of this research were teachers and students of MTs Mambaul Ulum Bata-bata 1 who were selected purposively. Data was collected through in-depth interviews, observation, and documentation. Source and time triangulation is used to see the validity of the data. The results of the study show that (1) the local wisdom values used to build religious moderation are the Pesantren tradition and the Toron tradition. (2) Efforts to build religious moderation are carried out by using the local wisdom of the pesantren, the culture of the madrasah, the exemplary clerics and teachers, compiling learning tools, and incorporating local wisdom values as PPKn subject matter. This research implies that religious moderation can be built with local wisdom values. This entire article can be used as a reference for further research by identifying exemplary forms and the application of religious moderation values by students in the community.